What are the functional outcomes of total laryngeal transplantation? A systematic review of preclinical and clinical studies - Henderson, Douglas; Knoedler, Leonard; Niederegger, Tobias; Fenske, Jakob; Mathieu, Olivier; Hundeshagen, Gabriel; Heiland, Max; Cetrulo, Curtis L.; Farwell, D. Gregory; Lechien, Jerome R.; Lellouch, Alexandre G. (Frontiers in Immunology, 2025)
PurposeThis systematic review aims to evaluate the functional outcomes of total laryngeal transplantation by synthesizing findings from both preclinical and clinical studies. It focuses on assessing postoperative functional recovery, including swallowing, airway patency, phonation, and speech, while also considering the associated morbidities and immunosuppressive strategies.MethodsA systematic review was conducted for functional outcomes of total laryngeal transplantation through PubMed/MEDLINE, Embase, Scopus, and Web of Science databases according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Case reports, case series, letters to the editor, reviews, and preclinical studies related to laryngeal transplantation were eligible for inclusion. Methodological quality and risk of bias were assessed via the CAMARADES checklist for preclinical studies and the JBI checklists for clinical studies.ResultsOut of n=188 identified studies, n=16 (8.5%) met the inclusion criteria. There were n=13 (81%) clinical and n=3 (19%) preclinical studies. In preclinical models, canine and minipig studies showed partial recovery: electrical stimulation restored vocal fold mobility in n=8 (40%) of canine allografts; some minipigs recovered swallowing, vocalization, and short-term survival post-transplant without immunosuppression, though all canines remained tracheostomy-dependent. Among n=18 (100%) human recipients, speech or phonation was restored fully or partially in n=12 (67%), as well as full or partial oral intake. Here, n=3 patients (17%) died within two years post-VCA, while n=4 (36%) resumed full oral intake. Voice quality was considered as satisfactory or better than pre-VCA in n=6 (55%) patients, whereas airway patency was deemed good or excellent. Nonetheless, no patient regained full vocal fold mobility. However, n=1 (5.6%) patient was able to breathe without a tracheostomy, and n=1 (5.6%) could intermittently cap their tracheostomy tube. Immunosuppressive regimens included tacrolimus (n=18, 100%), mycophenolate mofetil (n=15, 83%), corticosteroids (n=15, 83%), and anti-thymocyte globulin (n=6, 33%), with adjunctive use of leflunomide and stem cells in select cases.ConclusionLaryngeal transplantation shows promising results in restoring swallowing and phonation, but challenges remain for breathing without tracheostomy. The procedure remains an experimental surgery, still associated with significant morbidity and mortality, and requires lifelong immunosuppression. Future research, including long-term follow-up, larger-scale trials and interdisciplinary collaboration, is essential to further refine this procedure and evaluate its outcomes comprehensively.